Odontodysplasia involving single tooth: A rare entity - Mahesh Ramakrishnan; Padma Menon (Wolters Kluwer Medknow Publications, 2014)
Odontodysplasia is the developmental anomaly caused due to disturbances in the ectodermal and mesodermal component of the tooth. Although it involves multiple teeth in a quadrant, the involvement of a single tooth germ is very rare. The present report is a case of odontodysplasia involving a single maxillary central incisor.